Association between maternal occupational exposure to polycyclic aromatic hydrocarbons and rare birth defects of the face and central nervous system. Issue 5 (14th January 2020) - Santiago‐Colón, Albeliz; Rocheleau, Carissa M.; Chen, I‐Chen; Sanderson, Wayne; Waters, Martha A.; Lawson, Christina C.; Langlois, Peter H.; Cragan, Janet D.; Reefhuis, Jennita; ,
Abstract: Background: Previous studies suggested associations between maternal smoking, a source of exposure to polycyclic aromatic hydrocarbons (PAHs) and other chemicals, and central nervous system and face birth defects; however, no previous studies have evaluated maternal occupational PAH exposure itself. Methods: Jobs held in the periconceptional period were retrospectively assigned for occupational PAH exposures. Associations between maternal occupational PAH exposure and selected rare defects of the face (cataracts, microphthalmia, glaucoma, microtia, and choanal atresia) and central nervous system (holoprosencephaly, hydrocephaly, cerebellar hypoplasia, and Dandy‐Walker malformation) were evaluated using data from the National Birth Defects Prevention Study, a population‐based case–control study in the United States. Crude and adjusted odds ratios (ORs) with 95% confidence intervals were calculated to estimate associations between each evaluated defect and PAH exposure using multivariable logistic regression. Results: Food and beverage serving, as well as cooks and food preparation occupations, were among the most frequent jobs held by exposed mothers. Cataracts, microtia, microphthalmia, and holoprosencephaly were significantly associated with PAH exposure with evidence of dose–response ( P ‐values for trend ≤.05). Hydrocephaly was associated with any PAH exposure, but not significant for trend. Sensitivity analyses that reduced possible sources of exposure misclassification tended to strengthen associations. Conclusions: This is the first population‐based case–control study to evaluate associations between maternal occupational PAH exposures and these rare birth defects of the central nervous system and face.